2009
DOI: 10.1007/s11095-009-9837-y
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Multifunctional PLGA Nanoparticulate Drug Delivery System: Evaluation of its Physicochemical Properties and Anticancer Activity to Malignant Cancer Cells

Abstract: The developed multifunctional nanoparticles hold potential to treat malignant integrin-expressing cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 44 publications
5
51
0
1
Order By: Relevance
“…This integrin is recognized by the peptide sequence arginine-glycine-aspartic acid (RGD) [523,524]. Wang et al [525] angiogenic vessels [532,533]. The use of a tumor-homing peptide, iRGD, an RGD peptide that contains a tumor penetrating peptide (CendR or C-end rule), results in an optimized delivery of anticancer drugs deeply to the tumors.…”
Section: Peptidic Targetingmentioning
confidence: 99%
“…This integrin is recognized by the peptide sequence arginine-glycine-aspartic acid (RGD) [523,524]. Wang et al [525] angiogenic vessels [532,533]. The use of a tumor-homing peptide, iRGD, an RGD peptide that contains a tumor penetrating peptide (CendR or C-end rule), results in an optimized delivery of anticancer drugs deeply to the tumors.…”
Section: Peptidic Targetingmentioning
confidence: 99%
“…The nanoparticle targeting ability was enhanced via strong affinity to various integrin-expressing cancer cells, and much less affinity to low integrin-expressing cancer cells. 133 Danhier et al showed that PEGylated PLGAbased nanoparticles grafted with the RGD peptide or an RGD peptidomimetic, targeted the tumor endothelium and would enhance the antitumor efficacy of paclitaxel. They observed that RGD-grafted nanoparticles were more associated with human umbilical vein endothelial cells in vitro by binding to α v β 3 integrin than were nontargeted nanoparticles, and they also demonstrated the targeting of RGD and RGD peptidomimetic-grafted nanoparticles to tumor vessels, as well as effective retardation of transplantable liver tumor growth and prolonged survival times in mice treated by paclitaxel-loaded RGD nanoparticles when compared with nontargeted nanoparticles.…”
Section: Ligand-receptor Interactionmentioning
confidence: 99%
“…Activation of PHEMA-PLA to PHEMA-PLA-pNP was performed as described by Wang et al, 34 with some modifications. Briefly, 1.1 g of PHEMA-PLA was dissolved in 6 mL of chloroform by stirring, and then 0.5 g of pNP, 40 mg of 4-dimethylaminopyridine (dissolved in 6 mL of chloroform), and 1 mL of pyridine were added to the solution.…”
Section: Synthesis Of Phema-g-(pla-dppe) Copolymermentioning
confidence: 99%
“…11,12,14 In the present work, pNP was selected for activation of the PHEMA-PLA copolymer (Schema 1B) according to a previously reported method, with some changes. 34 The content of 4-nitrophenyl carbonate moieties could be determined during the reaction course. The degree of 4-nitrophenyl carbonate substitution could be controlled by adjusting the amount of chloroformate added.…”
Section: Dovepressmentioning
confidence: 99%